2000
DOI: 10.1002/1098-2396(200008)37:2<118::aid-syn6>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo regulation of ?-opioid receptor density and gene expression in CXBK and outbred Swiss Webster mice

Abstract: Chronic in vivo treatment with the opioid agonist etorphine downregulates -opioid receptor density, produces tolerance, and regulates gene expression in the mouse. After cessation of treatment, there is an increase in -opioid receptor mRNA level associated with the recovery of -opioid receptors. However, the effect of etorphine on the regulation of mRNA during treatment is currently not known. In this study, etorphine-induced changes in -opioid receptor density, mRNA, and opioid analgesic potency were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…⌻he density of central -opioid receptors in membrane homogenates from selected brain regions was measured using [ 3 H]DAMGO (5 nM) as a radioligand, essentially as described (26). D1 and D2 dopamine receptor levels were determined in the presence of 4 nM [ 3 H]SCH23390 and 2 nM [ 3 H]spiperone, respectively, following a published protocol (27).…”
Section: Methodscontrasting
confidence: 54%
“…⌻he density of central -opioid receptors in membrane homogenates from selected brain regions was measured using [ 3 H]DAMGO (5 nM) as a radioligand, essentially as described (26). D1 and D2 dopamine receptor levels were determined in the presence of 4 nM [ 3 H]SCH23390 and 2 nM [ 3 H]spiperone, respectively, following a published protocol (27).…”
Section: Methodscontrasting
confidence: 54%
“…However, the mechanisms involved in opioid receptor regulation after opioid agonist and antagonist treatment are different. For example, opioid agonist treatment is associated with changes in gene expression of opioid receptors (Kim et al, 1995;Sehba et al, 1997;Duttaroy and Yoburn, 2000) but antagonist treatment is not (Jenab et al, 1995;Unterwald et al, 1995;however, see Brodsky et al, 1995;Castelli et al, 1997;Duttaroy et al, 1999). Thus, it was not certain that GRK-2 and DYN-2 would be involved in opioid agonist-induced OR regulation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have examined the effect of chronic opioid agonists or their withdrawal on MOP-r mRNA levels in different brain regions (Brodsky et al 1995, Buzas et al 1996, Castelli et al 1997, Sehba et al 1997, Duttaroy & Yoburn 2000. The results obtained are conflicting; a decrease , Duttaroy & Yoburn 2000, an increase (Sehba et al 1997), or no change (Brodsky et al 1995, Buzas et al 1996, Castelli et al 1997 have been reported, and these apparently contradictory results may depend on differences in the brain regions examined, exposure time, dose, and route of the opioid agonist administered.…”
Section: Mop-r Mrna Responses In Acute Morphine Withdrawalmentioning
confidence: 99%
“…The results obtained are conflicting; a decrease , Duttaroy & Yoburn 2000, an increase (Sehba et al 1997), or no change (Brodsky et al 1995, Buzas et al 1996, Castelli et al 1997 have been reported, and these apparently contradictory results may depend on differences in the brain regions examined, exposure time, dose, and route of the opioid agonist administered. In many of the previous studies, morphine or opioid agonists were chronically administered by minipumps or pellets (Brodsky et al 1995, Sehba et al 1997, Duttaroy & Yoburn 2000. This differs from our morphine experiments using an intermittent pattern of administration, in which the animal could experience both rewarding effects and chronic stress induced by repeated morphine injection and withdrawal.…”
Section: Mop-r Mrna Responses In Acute Morphine Withdrawalmentioning
confidence: 99%